Contemporary History - TR122 - 202102 - Universidad Peruana de Ciencias Aplicadas (UPC) (2021)
Contemporary History is taught in English in the Translation and Interpreting Faculty to students in their second year at university. The course develops two main UPC competences: critical thinking and interculturality. Contemporary History covers a survey of the main historical events, political ideologies, economic upheavals and cultural changes which shaped Europe and other regions of the world in the 20th Century. It explores the causes that lead to the First and the Second World Wars and their consequences; it looks at internal affairs in Germany, the USA and the USSR in the twenties and thirties; analyses the effects of post-war peace settlements on the peoples of Europe, the Middle East and Asia; reveals the origins, developments and demise of the Cold War and how it has affected peoples around the world. It finally offers an overview of present day challenges and speculates about possible outcomes of today's international politics and society. The purpose of the course is to allow students become acquainted with events and circumstances that occurred before their times so that they can understand the impact these have on their lives today. It aims to show them how the past is linked to the present and shapes future situations. This knowledge will allow them to develop critical thinking skills as well as more specific skills related to their major such as intercultural awareness and empathy. Furthermore, the fact that it is taught in English contributes to the practice of a second language. Throughout the course they are expected to read, write, present orally and communicate in English at all times.